John Locke: bases metodológicas para alcanzar la certeza en el conocimiento de los principios prácticos - Ruiz-gallardón, Isabel (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2004)
Locke’s thought is characterized by its desire to build connections between the moral, intellectual and material worlds. He aims to establish the methodological grounds for a true knowledge of practical principles. Locke masterfully shapes the concepts of person, natural law, knowledge and property. A conjunction and full understanding of these concepts will lead men to a certain knowledge of the political and moral worlds. This study is the first in a comprehensive research line searching the so denied rational link between what «is» and what «ought to be».